Assessing the Downstream Contamination of Chemically Recycled Ethylene Feed Streams on the Kinetic Behavior of Ziegler‐Natta Catalysts and Microstructural Properties of HDPE and LLDPE. Issue 5 (1st September 2022) - Pernusch, Daniel Christian; Paulik, Christian; Mastalir, Matthias; Hofer, Wolfgang
Abstract: The sustainability of consumer materials, such as plastics, belongs to the most important aspect of eco‐efficiency analyses. Besides mechanical recycling, chemical recycling represents an interesting waste management pathway. In theory, this technique does not rely on single‐grade feedstock to maintain product quality. However, cross‐contamination of feedstocks potentially leads to above‐specification impurities in obtained pyrolysis oils. This study investigates the potential downstream poisoning of a fourth‐generation Ziegler‐Natta catalyst, using selected model poisons at high (worst‐case) concentrations. With experimental and computational analysis, economic feasibility factors such as catalyst activity and microstructural properties are evaluated during the synthesis of high‐density polyethylene (HDPE) and linear low‐density polyethylene (LLDPE). Noticeable effects on the catalyst activity can be observed when the poison interacts with the co‐catalyst, whereas a lower impact is observed for interactions with the activated catalyst‐co‐catalyst complex. Molecular weight distribution (MWD) and comonomer composition distribution (CCD) modeling highlighted marginal to no polymer property changes caused by contaminants. Combined with the applicability of pyrolysis post‐treatments, these observations show that chemical recycling can be a promising technique for post‐consumer plastic waste treatment. Abstract : Chemical recycling represents an interesting waste management pathway that can improve the sustainability of consumer materials, such as plastics. However, cross‐contamination of waste plastic feedstocks potentially leads to the above‐specified impurities in obtained pyrolysis oils. This study investigates the potential downstream poisoning of a fourth‐generation Ziegler‐Natta catalyst through experimental and computational analysis techniques.